2006
DOI: 10.1007/s00267-004-0179-6
|View full text |Cite
|
Sign up to set email alerts
|

The Interactive Effects of Fire and Diversity on Short-Term Responses of Ecosystem Processes in Experimental Mediterranean Grasslands

Abstract: We conducted a field experiment using constructed communities to test whether species richness contributed to the maintenance of ecosystem processes under fire disturbance. We studied the effects of diversity components (i.e., species richness and species composition) upon productivity, structural traits of vegetation, decomposition rates, and soil nutrients between burnt and unburnt experimental Mediterranean grassland communities. Our results demonstrated that fire and species richness had interactive effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…Dimitrakopoulos et al [52] showed that fire and species richness had interactive effects on above-ground biomass production, with fire increasing the biomass of species-rich communities. They also showed that species-rich communities are more resistant to fire than species-poor communities.…”
Section: Discussionmentioning
confidence: 99%
“…Dimitrakopoulos et al [52] showed that fire and species richness had interactive effects on above-ground biomass production, with fire increasing the biomass of species-rich communities. They also showed that species-rich communities are more resistant to fire than species-poor communities.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to other Greek islands (e.g. Genius et al 2008), the area currently faces drought problems, mainly during the summer months where high temperatures are recorded (Mean annual temperature: 17.6 • , average temperature of the warmest month (July): 26.5 • , average annual rainfall: 682 mm) (Dimitrakopoulos et al 2006). To confront water shortages during these periods, the authorities often suspend the water supply for approximately 2 h in different parts of the city.…”
Section: Description Of Research Areamentioning
confidence: 99%
“…In the Mediterranean Basin, higher diversity has been associated with more rapid recovery after fire (Lavorel, 1999). Fire effects also interact with species richness, increasing biomass production in rich communities (Dimitrakopoulos et al, 2006). In most MTEs, restoration of degraded environments due to human alteration could be facilitated by diversity of vegetation and associated soil microbes (García-Palacios et al, 2011;Viers et al, 2012).…”
Section: Species and Functional Diversitymentioning
confidence: 99%